Co-milling of glass forming ability class III drugs: Comparing the impact of low and high glass transition temperatures - Pätzmann, Nicolas; Beránek, Josef; Griffin, Brendan T; Kuentz, Martin; O'Dwyer, Patrick J (European journal of pharmaceutical sciences, 2025)
With an increasing focus on sustainable technologies in the pharmaceutical industry, milling provides a solvent-free approach to improve drug dissolution. Milling of drugs with an excipient offers additional opportunities to achieve supersaturation kinetics. Therefore, this work aims to present insights of co-milling fenofibrate and apremilast, two good glass formers with low and high glass transition temperatures (Tgs) respectively. Drugs were co-milled with croscarmellose sodium for various process durations followed by thermal analysis, investigation of crystallinity, surface area and dissolution. The dissolution enhancement of the low-Tg glass former fenofibrate highly correlated with the process-induced increase in surface area of co-milled systems (R2 = 0.96). In contrast, the high-Tg glass former apremilast lost its crystalline order gradually after ≥ 10 min of co-milling, and favourable supersaturation kinetics during biorelevant dissolution testing were observed. Interestingly, the melting point of co-milled apremilast decreased and linearly correlated with the highest measured drug concentration (cmax) during in vitro dissolution (onset temperature R2 = 0.98; peak temperature R2 = 0.96). The melting point depression remained stable after 90 days for apremilast, whereas fenofibrate co-milled for 20 min or more showed an increase in melting point upon storage. This study demonstrated that co-milling with croscarmellose sodium is ideally suited to good glass formers with a high Tg. The melting point depression is thereby proposed as an easily accessible critical quality attribute to estimate likely dissolution performance of drugs in dry co-milled formulations.
Keywords: Glass; Glass forming ability; Fenofibrate; thalidomid; Thalidomide; Aspirin; Drug supersaturation; Melting point depression; pomocné látky; Glass transition temperature; Solubility; Drug Liberation; rozpustnost; Co-milling; tranzitní teplota; příprava léků; Ball milling; Transition Temperature; sklo; fenofibrát; Croscarmellose sodium; Excipients; Drug Compounding; uvolňování léčiv